mRNA-COVID19 Vaccination Can Be Considered Safe and Tolerable for Frail Patients - Lupo-Stanghellini, Maria Teresa; Di Cosimo, Serena; Costantini, Massimo; Monti, Sara; Mantegazza, Renato; Mantovani, Alberto; Salvarani, Carlo; Zinzani, Pier Luigi; Inglese, Matilde; Ciceri, Fabio; Apolone, Giovanni; Ciliberto, Gennaro; et al. (Frontiers in Oncology, 2022)
Background Frail patients are considered at relevant risk of complications due to coronavirus disease 2019 (COVID-19) infection and, for this reason, are prioritized candidates for vaccination. As these patients were originally not included in the registration trials, fear related to vaccine adverse events and disease worsening was one of the reasons for vaccine hesitancy. Herein, we report the safety profile of the prospective, multicenter, national VAX4FRAIL study (NCT04848493) to evaluate vaccines in a large trans-disease cohort of patients with solid or hematological malignancies and neurological and rheumatological diseases. Methods Between March 3 and September 2, 2021, 566 patients were evaluable for safety endpoint: 105 received the mRNA-1273 vaccine and 461 the BNT162b2 vaccine. Frail patients were defined per protocol as patients under treatment with hematological malignancies (n = 131), solid tumors (n = 191), immune-rheumatological diseases (n = 86), and neurological diseases (n = 158), including multiple sclerosis and generalized myasthenia. The impact of the vaccination on the health status of patients was assessed through a questionnaire focused on the first week after each vaccine dose. Results The most frequently reported moderate–severe adverse events were pain at the injection site (60.3% after the first dose, 55.4% after the second), fatigue (30.1%–41.7%), bone pain (27.4%–27.2%), and headache (11.8%–18.9%). Risk factors associated with the occurrence of severe symptoms after vaccine administration were identified through a multivariate logistic regression analysis: age was associated with severe fever presentation (younger patients vs. middle-aged vs. older ones), female individuals presented a higher probability of severe pain at the injection site, fatigue, headache, and bone pain; and the mRNA-1237 vaccine was associated with a higher probability of severe pain at the injection site and fever. After the first dose, patients presenting a severe symptom were at a relevant risk of recurrence of the same severe symptom after the second one. Overall, 11 patients (1.9%) after the first dose and 7 (1.2%) after the second one required postponement or suspension of the disease-specific treatment. Finally, two fatal events occurred among our 566 patients. These two events were considered unrelated to the vaccine. Conclusions Our study reports that mRNA-COVID-19 vaccination is safe also in frail patients; as expected, side effects were manageable and had a minimum impact on patient care path.